Use of oscillating heat pipe technique as extended surface in wire-on-tube heat exchanger for heat transfer enhancement - Nuntaphan A. (2017)
This paper presents the performance of a wire-on-tube heat exchanger of which the wire is an oscillating heat pipe. The experiments for this heat exchanger were performed in a wind tunnel by exchanging heat between hot water flowing inside the heat exchanger tubes and air stream flowing across the external surface. R123, methanol and acetone were selected as working fluids of the oscillating heat pipe. The inlet water temperature was varied from 45 to 85 °C while the inlet air temperature was kept constant at 25 °C. The results show that the oscillating heat pipe technique for all working fluids could increase around 10% of the heat transfer rate obtained from that without the refrigerant flow in the capillary tube when the inlet water temperature is at 60 °C. Moreover, the heat transfer models for evaluating the heat exchanger effectiveness and the air-side heat transfer coefficient, are also developed in this work. These results of the models agreed very well with the experimental data. © 2009 Elsevier Ltd. All rights reserved.